White light emitting layer material and white light organic electroluminescent device

By using a white light emitting layer material composed of TADF main material and phosphorescent luminescent material, the problems of low efficiency and poor stability of existing white light OLED devices are solved, and a white light organic electroluminescent device with high efficiency, low voltage and excellent color stability are achieved.

CN119592321APending Publication Date: 2025-03-11CHANGCHUN INSTITUTE OF APPLIED CHEMISTRY CHINESE ACADEMY OF SCIENCES
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411702287.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-26
Publication Date
2025-03-11

AI Technical Summary

Technical Problem

Existing white light OLED devices have low efficiency, poor stability, and complex device structures lead to exciton quenching and efficiency roll-off problems.

Method used

A white light emitting layer material consisting of red, green and blue luminescent layers is used, specifically composed of TADF main material and phosphorescent luminescent material to ensure spectral coverage of 400nm to 780nm.

Benefits of technology

Lower light-on voltage, higher efficiency, lower efficiency roll-off, higher color rendering index, lower color temperature and excellent color stability are achieved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005153641850000031
    Figure BDA0005153641850000031
  • Figure BDA0005153641850000041
    Figure BDA0005153641850000041
  • Figure BDA0005153641850000051
    Figure BDA0005153641850000051
Patent Text Reader

Abstract

The invention discloses a white light emitting layer material and a white light organic electroluminescent device, and belongs to the technical field of organic electroluminescent devices. The white light emitting layer material is composed of a red light emitting layer, a green light emitting layer and a blue light emitting layer in sequence or composed of a yellow light emitting layer and a blue light emitting layer in sequence. The red light-emitting layer is composed of a TADF host material and a red phosphorescent light-emitting material; the green light-emitting layer is composed of a TADF host material and a green phosphorescent light-emitting material; the blue light-emitting layer is composed of a host material containing phosphorus-oxygen double bonds and a blue TADF light-emitting material; the yellow light-emitting layer is composed of a TADF host material and a yellow phosphorescent light-emitting material. The white light emitting layer material has spectrum coverage with the emission wavelength of 400-780 nm, and when the white light emitting layer material is applied to a white light organic electroluminescent device, the device has the advantages of low turn-on voltage, low color temperature, low efficiency roll-off, high efficiency, high color rendering index and excellent color stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of organic electroluminescent devices, and in particular to a white light emitting layer material and a white light organic electroluminescent device. Background Art

[0002] Organic light-emitting diode (OLED) is a new generation of lighting and display technology, which has the characteristics of low energy consumption, active light emission, ultra-thin, flexible, wide viewing angle, etc. As a lighting source, white light OLED has the characteristics of being green, environmentally friendly, and energy-saving. In addition, OLED is currently the only surface light source, which can easily improve the light utilization rate; OLED itself has the advantage of adjustable color, and it is easy to achieve more natural white light with a high color rendering index; white light OLED has no glare, strobe, and blue light hazards, which can better protect the human eye.

[0003] For white light OLEDs, the efficiency of white light OLED devices made of fluorescent materials is generally low. Due to the poor stability of short-wavelength blue phosphorescent materials, the stability of all-phosphorescent white light OLED devices is generally deviated. Therefore, the current design strategy is to combine blue fluorescent materials with long-wavelength green, yellow, and red phosphorescent materials to design fluorescent-phosphorescent hybrid white light OLED devices.

[0004] In 2006, Forrest et al. doped blue fluorescent materials, green and red phosphorescent materials into different light-emitting layers to prepare high-performance fluorescent-phosphorescent hybrid white light OLED devices. In order to prevent the blue fluorescent material from causing exciton quenching of the green and red phosphorescent materials, they inserted a spacer layer between the fluorescent material light-emitting layer and the phosphorescent material light-emitting layer. Although this method improves the spectral stability to a certain extent and also improves the device efficiency at low brightness. However, the insertion of the spacer layer inevitably increases the driving voltage and reduces the power efficiency of the device. In addition, since the exciton generation area is confined to a narrow luminous interval, as the current density increases, the excess excitons are annihilated; at the same time, such a device structure will increase the heterogeneous interface and increase the probability of exciton quenching at the interface, resulting in a significant roll-off of the device efficiency at high brightness. In 2013, Ma Dongge, a researcher at the Changchun Institute of Applied Chemistry, and others controlled the carrier recombination area within the blue fluorescent light-emitting layer by mixing the main body, rationally regulated the exciton distribution, and avoided the use of the spacer layer, thereby preparing a high-performance fluorescent-phosphorescent hybrid white light OLED device. However, since some triplet excitons are formed on the blue fluorescent molecules and cannot be effectively utilized, the device efficiency is still low. In 2016, researcher Ma Dongge and others improved the device structure, replaced the blue fluorescent material with a blue TADF material, and designed a device structure with continuous energy transfer, achieving a fluorescent-phosphorescent hybrid white light OLED device with high efficiency, high color rendering index, high color stability, and low efficiency roll-off. However, the obtained device requires a higher turn-on voltage, and the device efficiency needs to be further improved. In addition, for white light OLED devices, the improvement of one performance will lead to the decline of another performance. In most cases, higher device efficiency and excellent luminescent color quality cannot be met at the same time.

[0005] Therefore, it is of great significance to research and develop a new type of white light emitting layer material and white light organic electroluminescent device. Summary of the invention

[0006] In view of this, the technical problem to be solved by the present invention is to provide a white light emitting layer material and a white light organic electroluminescent device. The white light emitting layer material has a spectrum coverage of emission wavelengths from 400nm to 780nm, and is applied to a white light organic electroluminescent device so that the device has a lower turn-on voltage, higher efficiency, lower efficiency roll-off, higher color rendering index, lower color temperature, and excellent color stability.

[0007] In order to achieve the above purpose, the technical solution adopted by the present invention is as follows:

[0008] The present invention provides a white light emitting layer material, which is composed of a red light emitting layer, a green light emitting layer, and a blue light emitting layer in sequence, or a yellow light emitting layer and a blue light emitting layer in sequence;

[0009] The red light-emitting layer is composed of a TADF main material and a red phosphorescent light-emitting material;

[0010] The green light-emitting layer is composed of a TADF main material and a green phosphorescent light-emitting material;

[0011] The blue light-emitting layer is composed of a host material containing a phosphorus-oxygen double bond and a blue TADF light-emitting material;

[0012] The yellow light-emitting layer is composed of a TADF main material and a yellow phosphorescent light-emitting material.

[0013] Preferably, the TADF main material is selected from 2,4-diphenyl-6-bis((12-phenylindole)[2,3-a]carbazole-11-yl)-1,3,5-triazine (abbreviated as DIC-TRZ), 11-(3-(4,6-di([1,1'-biphenyl]-3-yl)-1,3,5-triazine-2-yl)phenyl)-12,12-dimethyl-11,12-dihydroindeno[2,1-a]carbazole (abbreviated as DPDDC-2Ph), 11-(4,6-di(biphenyl-4-yl)-1,3,5-triazine-2-yl)-12-phenyl-11,12-dihydroindole[2,3-a]carbazole (abbreviated as p-DIC-TRZ-2Ph), 11-(4,6-di(biphenyl-3-yl)-1,3,5-triazine-2-yl)-12-phenyl-11,12-dihydroindole[2,3-a]carbazole (abbreviated as m-DIC- TRZ-2Ph), 5-(3-(4,6-diphenyl-1,3,5-triazine-2-yl)phenyl)-7,7-dimethyl-5,7-dihydroindeno[2,1-b]carbazole (abbreviated as DMIC-TRZ), 5-(4,6-diphenyl-1,3,5-triazine-2-yl)-11-phenyl-5,11-dihydroindeno[3,2-b]carbazole (abbreviated as pIC-TRZ), 9-(4-(4,6-diphenyl)-1,3,5-triazine-2-yl)phenyl)-7,7-dimethyl-5,7-dihydroindeno[2,1-b]carbazole (abbreviated as DMIC-TRZ), One or more of 2-(3-(4,6-diphenyl-1,3,5-triazine-2-yl)phenyl)-9H-carbazole (abbreviated as Cab-Ph-TRZ), 2-(3-(4,6-diphenyl-1,3,5-triazine-2-yl)phenyl)-1-phenyl-1H-benzo[d]imidazole (abbreviated as PIM-TRZ), and 3-[3-(9H-carbazole-9-yl)phenyl]furo[2,3-b:5,4-b']bipyridine (abbreviated as 3CzPFP);

[0014] Its molecular structure is shown below:

[0015]

[0016]

[0017] The main material containing phosphorus-oxygen double bonds in the blue light-emitting layer is selected from one or more of 2,8-bis(diphenylphosphoryl)dibenzo[b,d]furan (PPF for short), bis[2-(diphenylphosphino)phenyl]ether oxide (DPEPO for short), diphenyl-4-triphenylsilyl-phenyl-phosphine oxide (TSPO1 for short), dibenzofuran-4-yl-diphenyl-phosphine oxide (DBFPPO for short), 9,9-spirobifluorene-4-yl-diphenyl-phosphine oxide (SPPO11 for short), 9-(3,5-bis(diphenylphosphoryl)phenyl)-9H-carbazole (CzPO2 for short), and 2,8-bis(diphenylphosphoryl)dibenzo[b,d]thiophene (PPT for short); more preferably 2,8-bis(diphenylphosphoryl)dibenzo[b,d]furan (PPF for short).

[0018] Its molecular structure is shown below:

[0019]

[0020] Preferably, the red phosphorescent luminescent material is selected from bis(2-benzo[b]thiophene-2-ylpyridine)(acetylacetonate)iridium(III) (abbreviated as Ir(btp)2(acac)), tris(1-phenylisoquinoline)iridium(III) (abbreviated as Ir(piq)3), bis(2-phenylquinoline)(2,2,6,6-tetramethylheptane-3,5-dioate)iridium(III) (abbreviated as PQ2Ir(dpm)), bis(phenylisoquinoline)(2,2,6,6-tetramethylheptane-3,5-dioate)iridium(III) (abbreviated as PQ2Ir(dpm)), Abbreviated as Ir(dpm)(piq)2), bis(2-methyldibenzo[f,h]quinoxaline)(acetylacetonate)iridium(III) (abbreviated as Ir(MDQ)2(acac)), bis(2-(3,5-dimethylphenyl)quinoline-C2,N')(acetylacetonate)iridium(III) (abbreviated as Ir(dmpq)2(acac)), bis[2-(3,5-dimethylphenyl)-4-methylquinoline](acetylacetonate)iridium(III) (abbreviated as Ir(mphmq)2(acac)).

[0021] Its molecular structure is shown below:

[0022]

[0023] Preferably, the green phosphorescent luminescent material is selected from one or more of bis(2-phenylpyridine)(acetylacetonate)iridium(III) (abbreviated as Ir(ppy)2(acac)), tris[2-(p-tolyl)pyridine]iridium(III) (abbreviated as Ir(mppy)3), bis(2-(3,5-dimethylphenyl)-4-propylpyridine)(2,2,6,6-tetramethylheptane-3,5-diketonate)iridium(III) (abbreviated as Ir(dmppy-pro)2tmd), bis(2-(naphthalene-2-yl)pyridine)(acetylacetonate)iridium(III) (abbreviated as Ir(npy)2(acac)), [2-(4-methyl-5-phenyl-2-pyridyl-KN)phenyl KC]bis[2-(2-pyridyl-KN)phenyl KC]iridium (abbreviated as Ir(ppy)2(bpmp));

[0024] Its molecular structure is shown below:

[0025]

[0026] Preferably, the blue TADF luminescent material is selected from 10-(2,12-di-tert-butyl-5,9-dioxa-13b-boronaphtho[3,2,1-de]anthracen-7-yl)-9,9-dimethyl-9,10-dihydroacridine (abbreviated as TDBA-Ac), 5-(2,12-di-tert-butyl-5,9-dioxa-13b-boronaphtho[3,2,1de]anthracen-7-yl)-10,15-diphenyl-10,15-dihydro-5H-diindole[3,2-a :3',2'-c]carbazole (abbreviated as TDBA–DI), 9'-(2,12-di-tert-butyl-5,9-dioxa-13b-boronaphthyl-[3,2,1de]anthracen-7-yl)-9,9'-diphenyl-9H,9'H,9'-H-3,3':6',3'-dicarbazole (abbreviated as TB-P3Cz), 10,10'-(4,4'-sulfonylbis(4,1-phenylene))bis(9,9-dimethyl-9,10-dihydroacridine) (abbreviated as DMA C-DPS), 9'-[4-(4,6-diphenyl-1,3,5-triazine-2-yl)phenyl]-3,3", 6,6'-tetraphenyl-9,3':6',9'-tert-9H-carbazole (abbreviated as BDPCC-TPTA), (9'-(2,12-di-tert-butyl-5,9-dioxa-13b-boronaphtho[3,2,1-de]anthracen-7-yl)-9'H-9,3':6',9'-dicarbazole (abbreviated as TB-3Cz), 5-(3,1 One or more of 1-dimethyl-5,9-dioxa-13b-boronaphtho[3,2,1-de]anthracene-7-yl)-10,15-diphenyl-10,15-dihydro-5H-diindol[3,2-a:3',2'-c]carbazole (abbreviated as mMDBA-DI), 3,11-bis(1,3,6,8-tetramethyl-9H-carbazole-9-yl)-5,9-dioxo-13b-boronaphtho[3,2,1-de]anthracene (abbreviated as DBA-DTMCz);

[0027] Its molecular structure is shown below:

[0028]

[0029] Preferably, the yellow phosphorescent luminescent material is selected from bis(2-(3,5-dimethylphenyl)-4-phenylpyridine)(2,2,6,6-tetramethylheptane-3,5-diketonate)iridium(III) (abbreviated as Ir(dmppy-ph)2tmd), iridium(III)acetylacetonatebis(4-(4-tert-butylphenyl)thieno[3,2-c]pyridinyl-N,C2') (abbreviated as PO-01-TB), bis(4-phenylthieno[3,2-c]pyridinyl-N,C2')(acetylacetonate)iridium(III) II) (abbreviated as PO-01), bis(2-(2,4-difluorophenyl)quinoline)picolinate iridium(III) (abbreviated as FPQIrpic), bis(2-(9,9-diethylfluoren-2-yl)-1-phenyl-1H-benzo[d]imidazole)(acetylacetonate)iridium(III) (abbreviated as Ir(fbi)2(acac)), acetylacetonate iridium(III)bis(4-(4-tert-butylphenyl)thieno[3,2-c]pyridinyl-N,C2′) (abbreviated as Ir(tptpy)2acac).

[0030] Its molecular structure is shown below:

[0031]

[0032] It is further preferred in the present invention that the red phosphorescent luminescent material is selected from bis(2-phenylquinoline)(2,2,6,6-tetramethylheptane-3,5-dioate)iridium(III);

[0033] Further preferably, the green phosphorescent luminescent material is selected from tris[2-(p-tolyl)pyridine]iridium(III);

[0034] Further preferably, the blue TADF luminescent material is selected from 5-(2,12-di-tert-butyl-5,9-dioxa-13b-boronaphtho[3,2,1de]anthracene-7-yl)-10,15-diphenyl-10,15-dihydro-5H diindolyl[3,2-a:3',2'-c]carbazole;

[0035] Further preferably, the yellow phosphorescent light-emitting material is selected from bis(2-(3,5-dimethylphenyl)-4-phenylpyridine)(2,2,6,6-tetramethylheptane-3,5-diketonate)iridium(III).

[0036] It is further preferred that the red light-emitting layer is composed of bis(2-phenylquinoline)(2,2,6,6-tetramethylheptane-3,5-dioate)iridium(III) and 2,4-diphenyl-6-bis((12-phenylindole)[2,3-a]carbazole-11-yl)-1,3,5-triazine;

[0037] More preferably, the green light-emitting layer is composed of tris[2-(p-tolyl)pyridine]iridium(III) and 2,4-diphenyl-6-bis((12-phenylindole)[2,3-a]carbazole-11-yl)-1,3,5-triazine;

[0038] More preferably, the blue light-emitting layer is composed of 5-(2,12-di-tert-butyl-5,9-dioxa-13b-boronaphtho[3,2,1de]anthracene-7-yl)-10,15-diphenyl-10,15-dihydro-5H diindole[3,2-a:3',2'-c]carbazole and 2,8-bis(diphenylphosphoryl)dibenzo[b,d]furan;

[0039] More preferably, the yellow light-emitting layer is composed of bis(2-(3,5-dimethylphenyl)-4-phenylpyridine)(2,2,6,6-tetramethylheptane-3,5-dionatoic acid)iridium(III) and 2,4-diphenyl-6-bis((12-phenylindole)[2,3-a]carbazole-11-yl)-1,3,5-triazine.

[0040] Preferably, the content of the red phosphorescent material in the red light-emitting layer is 1 wt% to 10 wt%;

[0041] Preferably, the content of the green phosphorescent material in the green light-emitting layer is 1wt% to 25wt%;

[0042] Preferably, the content of the blue TADF luminescent material in the blue luminescent layer is 5wt% to 50wt%;

[0043] Preferably, the content of the yellow phosphorescent material in the yellow light emitting layer is 1 wt% to 20 wt%.

[0044] Preferably, the thickness of the red light-emitting layer is selected from 2-20 nm;

[0045] Preferably, the thickness of the green light-emitting layer is selected from 2-20 nm;

[0046] Preferably, the thickness of the blue light-emitting layer is selected from 5-40 nm;

[0047] Preferably, the thickness of the yellow light emitting layer is selected from 1-30 nm.

[0048] The present invention also provides a white light organic electroluminescent device, comprising the above-mentioned white light emitting layer material.

[0049] Preferably, the white light organic electroluminescent device further comprises a hole transport layer / electron blocking layer, a hole transport layer, and a hole injection layer sequentially connected below the white light emitting layer material, and a hole blocking layer / electron transport layer and an electron injection layer sequentially connected above the white light emitting layer material.

[0050] The hole transport layer / electron blocking layer is selected from one or more of 4,4',4"-tri(carbazole-9-yl)triphenylamine (TCTA), 9,9'-(1,3-phenyl)di-9H-carbazole (MCP), 4,4'-bis(carbazole-9-yl)biphenyl (CBP), and 9-(4-tert-butylphenyl)-3,6-bis(triphenylsilyl)-9H-carbazole (CzSi).

[0051] The molecular structures are shown below:

[0052]

[0053] The hole blocking layer / electron transport layer is selected from 2,8-bis(diphenylphosphoryl)dibenzo[b,d]furan (PPF for short), 1,3,5-tris(6-(3-(pyridin-3-yl)phenyl)pyridin-2-yl)benzene (Tm3PyP26PyB for short), 2,4,6-tris(3'-(pyridin-3-yl)biphenyl-3-yl)-1,3,5-triazine (TmPPPyTz for short), 1,3,5-tris[(3-pyridine)-3-phenyl]benzene (TmPyPB for short), and 1,3,5-tris(1-phenyl-1H-benzimidazol-2-yl)benzene (TPBi for short), and its molecular structure is shown below:

[0054]

[0055] The hole transport layer is selected from one or more of 4,4'-cyclohexylbis[N,N'-bis(4-methylphenyl)aniline] (TAPC for short), tris(4-(quinolin-8-yl)phenyl)amine (TQTPA for short), N,N'-bis(naphthalene-1-yl)-N,N'-bis(phenyl)-benzidine (NPB for short), and N,N'-bis(3-methylphenyl)-N,N'-bis(phenyl)-benzidine (TPD for short); their molecular structures are shown below:

[0056]

[0057] The hole injection layer is selected from dipyrazino[2,3-f:2',3'-h]quinoxaline-2,3,6,7,10,11-hexanenitrile (HAT-CN for short), copper phthalocyanine (II) (CuPc for short), 2,3,5,6-tetrafluoro-7,7,8,8-tetracyano-quinodimethane (F4-TCNQ for short), 7,7,8,8-tetracyanoquinodimethane (TCNQ for short), and their molecular structures are shown below:

[0058]

[0059] The electron injection layer is selected from one or more of lithium fluoride (LiF), 8-hydroxyquinoline lithium (Liq for short) or lithium carbonate (Li2CO3).

[0060] The above-mentioned white light organic electroluminescent device also includes a metal cathode layer and an anode layer. The metal cathode layer includes but is not limited to the following materials: metal aluminum (Al), metal silver (Ag), metal magnesium (Mg), etc.; the anode layer includes but is not limited to indium tin oxide (ITO).

[0061] Preferably, the surface resistance of the ITO is 5 to 25 ohms.

[0062] Preferably, the hole injection layer has a thickness of 2-10 nm.

[0063] Preferably, the hole transport layer has a thickness of 30-70 nm.

[0064] Preferably, the thickness of the hole transport layer / electron blocking layer is 5-30 nm.

[0065] Preferably, the thickness of the hole blocking layer / electron transport layer is 40-80 nm.

[0066] Preferably, the thickness of the electron injection layer is 0.6-1.5 nm.

[0067] Preferably, the thickness of the metal cathode layer is 80-200 nm.

[0068] The present invention also provides the application of the white light organic electroluminescent device in eye protection lamps and vehicle lighting lamps.

[0069] Compared with the prior art, the white light emitting layer material provided by the present invention is composed of a red light emitting layer, a green light emitting layer, and a blue light emitting layer in sequence or a yellow light emitting layer and a blue light emitting layer in sequence; the red light emitting layer is composed of a TADF main material and a red phosphorescent light emitting material; the green light emitting layer is composed of a TADF main material and a green phosphorescent light emitting material; the blue light emitting layer is composed of a main material containing a phosphorus oxygen double bond and a blue TADF light emitting material; the yellow light emitting layer is composed of a TADF main material and a yellow phosphorescent light emitting material. The white light emitting layer material of the present invention has a spectrum coverage of an emission wavelength from 400-780nm, and its application in a white light organic electroluminescent device enables the device to have a lower turn-on voltage, higher efficiency, lower efficiency roll-off, higher color rendering index, lower color temperature, and excellent color stability. BRIEF DESCRIPTION OF THE DRAWINGS

[0070] Figure 1 Schematic diagram of the structure of the device of Example 1 of the present invention, 1 is a glass substrate, 2 is an anode layer, 3 is a hole injection layer, 4 is a hole transport layer, 5 is a hole transport layer / electron blocking layer, 6 is a red light-emitting layer, 7 is a green light-emitting layer, 8 is a blue light-emitting layer, 9 is a hole blocking layer / electron transport layer, 10 is an electron injection layer, and 11 is a metal cathode layer;

[0071] Figure 2 The characteristic curve of current efficiency-power efficiency-brightness of the white organic electroluminescent device prepared in Example 1;

[0072] Figure 3 The characteristic curve of external quantum efficiency-current density of the white light organic electroluminescent device prepared in Example 1;

[0073] Figure 4 The white light organic electroluminescent device prepared in Example 1 has a brightness of 1000 cd / m 2 , 2000cd / m 2 , 5000cd / m 2 and 10000cd / m 2 Spectrum diagram when

[0074] Figure 5 is a brightness-current density-voltage characteristic curve of the white light organic electroluminescent device prepared in Example 1;

[0075] Figure 6 Schematic diagram of the structure of the device of Example 2 of the present invention, 1 is a glass substrate, 2 is an anode layer, 3 is a hole injection layer, 4 is a hole transport layer, 5 is a hole transport layer / electron blocking layer, 6 is a red light-emitting layer, 7 is a green light-emitting layer, 8 is a blue light-emitting layer, 9 is a hole blocking layer / electron transport layer, 10 is an electron transport layer, 11 is an electron injection layer, and 12 is a metal cathode layer;

[0076] Figure 7 The characteristic curve of current efficiency-power efficiency-brightness of the white light organic electroluminescent device prepared in Example 2;

[0077] Figure 8 The characteristic curve of external quantum efficiency-current density of the white light organic electroluminescent device prepared in Example 2;

[0078] Fig. 9 The white light organic electroluminescent device prepared in Example 2 has a brightness of 1000 cd / m 2 , 2000cd / m 2 , 5000cd / m 2 and 10000cd / m 2 Spectrum diagram when

[0079] Fig.10 is a brightness-current density-voltage characteristic curve of the white light organic electroluminescent device prepared in Example 2;

[0080] Fig.11 Schematic diagram of the structure of the device of Example 3 of the present invention, 1 is a glass substrate, 2 is an anode layer, 3 is a hole injection layer, 4 is a hole transport layer, 5 is a hole transport layer / electron blocking layer, 6 is a yellow light-emitting layer, 7 is a blue light-emitting layer, 8 is a hole blocking layer / electron transport layer, 9 is an electron transport layer, 10 is an electron injection layer, and 11 is a metal cathode layer;

[0081] Fig.12 The characteristic curve of current efficiency-power efficiency-brightness of the white organic electroluminescent device prepared in Example 3;

[0082] Fig.13 The characteristic curve diagram of external quantum efficiency-current density of the white light organic electroluminescent device prepared in Example 3;

[0083] Fig.14 The white light organic electroluminescent device prepared in Example 3 has a brightness of 1000 cd / m 2 , 2000cd / m 2 and 5000cd / m 2 Spectrum diagram when

[0084] Fig.15 is a brightness-current density-voltage characteristic curve of the white light organic electroluminescent device prepared in Example 3;

[0085] Fig.16Schematic diagram of the structure of the device of Example 4 of the present invention, 1 is a glass substrate, 2 is an anode layer, 3 is a hole injection layer, 4 is a hole transport layer, 5 is a hole transport layer / electron blocking layer, 6 is a yellow light-emitting layer, 7 is a blue light-emitting layer, 8 is a hole blocking layer / electron transport layer, 9 is an electron injection layer, and 10 is a metal cathode layer;

[0086] Fig.17 The characteristic curve of current efficiency-power efficiency-brightness of the white organic electroluminescent device prepared in Example 4;

[0087] Fig.18 The characteristic curve of external quantum efficiency-current density of the white light organic electroluminescent device prepared in Example 4;

[0088] Fig.19 The white light organic electroluminescent device prepared in Example 4 has a brightness of 1000 cd / m 2 , 2000cd / m 2 and 5000cd / m 2 Spectrum diagram when

[0089] Fig. 20 is a brightness-current density-voltage characteristic curve of the white light organic electroluminescent device prepared in Example 4;

[0090] Fig.21 Schematic diagram of the structure of the device of Example 5 of the present invention, 1 is a glass substrate, 2 is an anode layer, 3 is a hole injection layer, 4 is a hole transport layer, 5 is a hole transport layer / electron blocking layer, 6 is a red light-emitting layer, 7 is a green light-emitting layer, 8 is a blue light-emitting layer, 9 is a hole blocking layer / electron transport layer, 10 is an electron transport layer, 11 is an electron injection layer, and 12 is a metal cathode layer;

[0091] Fig. 22 The current efficiency-current density-power efficiency characteristic curve of the white light device prepared in Example 5;

[0092] Fig.23 The external quantum efficiency-current density characteristic curve of the white light device prepared in Example 5;

[0093] Fig.24 The white light device prepared in Example 5 has a brightness of 1000 cd / m 2 , 2000cd / m 2 , 5000cd / m 2 、10000cd / m 2 and 20000cd / m 2 Spectrum diagram when

[0094] Fig.25This is a brightness-current density-voltage characteristic curve of the device in Example 5. DETAILED DESCRIPTION

[0095] In order to further illustrate the present invention, the white light emitting layer material and the white light organic electroluminescent device provided by the present invention are described in detail below in conjunction with the embodiments.

[0096] Example 1

[0097] First, the ITO glass with patterns was cleaned with cleaning solution and deionized water for 15 minutes and then placed in an oven for drying. Then, the dried substrate was placed in a pretreatment vacuum chamber and then transferred to an organic evaporation chamber. -5 In an organic evaporation chamber of 1000 Å, a 6-nm-thick HAT-CN hole injection layer 3, a 50-nm-thick TAPC hole transport layer 4, a 10-nm-thick TCTA hole transport layer / electron blocking layer 5, a 3-nm-thick PQ2Ir(dpm) and DIC-TRZ-doped red light-emitting layer 6, a 3-nm-thick Ir(mppy)3 and DIC-TRZ-doped green light-emitting layer 7, a 15-nm-thick TDBA-DI and PPF-doped blue light-emitting layer 8, and a 50-nm-thick Tm3PyP26PyB hole blocking layer / electron transport layer 9 were sequentially deposited on the ITO layer. Next, the unfinished device was transferred to a metal evaporation chamber and deposited at a temperature less than 1.0×10 -5A 1 nm thick LiF electron injection layer 10 is evaporated in a vacuum atmosphere of 300 Pa, and finally a 100 nm thick Al metal cathode layer 11 is evaporated on the LiF layer through a special mask to prepare a white organic electroluminescent device with a structure of ITO / HAT-CN / TAPC / TCTA / PQ2Ir(dpm)(3wt%):DIC-TRZ / Ir(mppy)3(10wt%):DIC-TRZ / TDBA-DI(25wt%):PPF / Tm3PyP26PyB / LiF / Al. The evaporation rate of HAT-CN in the hole injection layer 3 was controlled at 0.01 nm / s, the evaporation rate of TAPC in the hole transport layer 4 was controlled at 0.05 nm / s, the evaporation rate of TCTA in the hole transport layer / electron blocking layer 5 was controlled at 0.05 nm / s, the evaporation rates of PQ2Ir(dpm) and DIC-TRZ in the red light-emitting layer 6 were controlled at 0.0015 nm / s and 0.05 nm / s, respectively, and the evaporation rates of Ir(mppy)3 and DIC-TRZ in the green light-emitting layer 7 were controlled at 0.0015 nm / s and 0.05 nm / s, respectively. The evaporation rates are controlled at 0.005 nm / s and 0.05 nm / s respectively, the evaporation rates of TDBA-DI and PPF in the blue light-emitting layer 8 are controlled at 0.0125 nm / s and 0.05 nm / s respectively, the evaporation rate of Tm3PyP26PyB in the hole blocking layer / electron transport layer 9 is controlled at 0.05 nm / s, the evaporation rate of LiF in the electron injection layer 10 is controlled at 0.005 nm / s, and the evaporation rate of Al in the metal cathode layer 11 is controlled at 0.5 nm / s.

[0098] Figure 1 This is a schematic diagram of the structure of the white light device prepared in Example 1, in which the white light device uses TADF material as the main body of red and green phosphorescent emission materials and blue TADF material as the blue light-emitting unit, and is composed of a glass substrate 1, an anode layer 2, a hole injection layer 3, a hole transport layer 4, a hole transport layer / electron blocking layer 5, a red light-emitting layer 6, a green light-emitting layer 7, a blue light-emitting layer 8, a hole blocking layer / electron transport layer 9, an electron injection layer 10 and a metal cathode layer 11 which are connected in sequence. Figure 2 The current efficiency-current density-power efficiency characteristic curve of the white light device prepared in Example 1 shows that the maximum current efficiency of the white light device is 63.91 candelas / ampere (cd / A), and the maximum power efficiency is 64.73 lumens / watt (lm / W). Figure 3 The external quantum efficiency-current density characteristic curve of the device shows that the maximum external quantum efficiency of the device is 28.57%. In addition, at a brightness of 1000 candelas / square meter, the current efficiency of the device is 40.47 candelas / ampere (cd / A), the power efficiency is 28.24 lumens / watt (lm / W), and the external quantum efficiency is 18.34%. Figure 4The white light device prepared in Example 1 has a brightness of 1000 cd / m 2 , 2000cd / m 2 , 5000cd / m 2 and 10000cd / m 2 The spectrum diagram shows that the three main emission peaks in the spectrum are located at 476, 504 and 596 nanometers, the device color coordinates are (0.410, 0.408), (0.406, 0.407), (0.396, 0.404) and (0.390, 0.402), and the color rendering index is 81.

[0099] Figure 5 The brightness-current density-voltage characteristic curve of the white light device in Example 1 shows that the lighting voltage of the device is 2.6 volts and the maximum brightness of the device is 56064 cd / m 2 .

[0100] Example 2

[0101] First, the ITO glass with patterns was cleaned with cleaning solution and deionized water for 15 minutes and then placed in an oven for drying. Then, the dried substrate was placed in a pretreatment vacuum chamber and then transferred to an organic evaporation chamber. -5 In an organic evaporation chamber at 1000 rpm, a 6-nm-thick HAT-CN hole injection layer 3, a 50-nm-thick TAPC hole transport layer 4, a 10-nm-thick TCTA hole transport layer / electron blocking layer 5, a 3-nm-thick PQ2Ir(dpm) and DIC-TRZ-doped red light-emitting layer 6, a 3-nm-thick Ir(mppy)3 and DIC-TRZ-doped green light-emitting layer 7, a 15-nm-thick TDBA-DI and PPF-doped blue light-emitting layer 8, a 5-nm-thick PPF hole blocking layer / electron transport layer 9, and a 50-nm-thick Tm3PyP26PyB electron transport layer 10 were sequentially deposited on the ITO layer. Next, the unfinished device was transferred to a metal evaporation chamber and deposited at a temperature less than 1.0×10 -5A 1 nm thick LiF electron injection layer 11 is evaporated in a vacuum atmosphere of 300 Pa, and finally a 100 nm thick Al metal cathode layer 12 is evaporated on the LiF layer through a special mask to prepare a white organic electroluminescent device with a structure of ITO / HAT-CN / TAPC / TCTA / PQ2Ir(dpm)(3wt%):DIC-TRZ / Ir(mppy)3(8wt%):DIC-TRZ / TDBA-DI(25wt%):PPF / PPF / Tm3PyP26PyB / LiF / Al. The evaporation rate of HAT-CN in the hole injection layer 3 was controlled at 0.01 nm / s, the evaporation rate of TAPC in the hole transport layer 4 was controlled at 0.05 nm / s, the evaporation rate of TCTA in the hole transport layer / electron blocking layer 5 was controlled at 0.05 nm / s, the evaporation rates of PQ2Ir(dpm) and DIC-TRZ in the red light-emitting layer 6 were controlled at 0.0015 nm / s and 0.05 nm / s, respectively, and the evaporation rates of Ir(mppy)3 and DIC-TRZ in the green light-emitting layer 7 were controlled at 0.004 nm / s, respectively. The evaporation rates of TDBA-DI and PPF in the blue light-emitting layer 8 are controlled at 0.0125 nm / s and 0.05 nm / s respectively, the evaporation rate of PPF in the hole blocking layer / electron transport layer 9 is controlled at 0.05 nm / s, the evaporation rate of Tm3PyP26PyB in the electron transport layer 10 is controlled at 0.05 nm / s, the evaporation rate of LiF in the electron injection layer 11 is controlled at 0.005 nm / s, and the evaporation rate of Al in the metal cathode layer 12 is controlled at 0.5 nm / s.

[0102] Figure 6 It is a structural schematic diagram of a white light device, in which TADF material is used as the main body of red and green phosphorescent emission materials and blue TADF material is used as the blue light-emitting unit, and the device is composed of a glass substrate 1, an anode layer 2, a hole injection layer 3, a hole transport layer 4, a hole transport layer / electron blocking layer 5, a red light-emitting layer 6, a green light-emitting layer 7, a blue light-emitting layer 8, a hole blocking layer / electron transport layer 9, an electron transport layer 10, an electron injection layer 11 and a metal cathode layer 12 which are connected in sequence.

[0103] Figure 7 This is a current efficiency-current density-power efficiency characteristic curve of the white light device prepared in Example 2. The results show that the maximum current efficiency of the white light device is 60.04 candelas / ampere (cd / A), and the maximum power efficiency is 65.57 lumens / watt (lm / W). Figure 8The external quantum efficiency-current density characteristic curve of the device shows that the maximum external quantum efficiency of the device is 28.01%. In addition, at a brightness of 1000 candelas / square meter, the current efficiency of the device is 45.03 candelas / ampere (cd / A), the power efficiency is 33.67 lumens / watt (lm / W), and the external quantum efficiency is 21.24%. Fig. 9 The white light device prepared in Example 2 has a brightness of 1000 cd / m 2 , 2000cd / m 2 , 5000cd / m 2 and 10000cd / m 2 The spectrum diagram shows that the three main emission peaks in the spectrum are located at 476, 504 and 596 nanometers, the device color coordinates are (0.405, 0.388), (0.399, 0.386), (0.390, 0.383) and (0.384, 0.381), the color rendering index is 77 and the color temperature is 3492K.

[0104] Fig.10 The brightness-current density-voltage characteristic curve of the device in Example 2 shows that the turn-on voltage of the device is 2.6V and the maximum brightness of the device is 61308cd / m 2 .

[0105] Example 3

[0106] First, the ITO glass with patterns was cleaned with cleaning solution and deionized water for 15 minutes and then placed in an oven for drying. Then, the dried substrate was placed in a pretreatment vacuum chamber and then transferred to an organic evaporation chamber. -5 In an organic evaporation chamber at 1000 rpm, a 6-nm-thick HAT-CN hole injection layer 3, a 50-nm-thick TAPC hole transport layer 4, a 10-nm-thick TCTA hole transport layer / electron blocking layer 5, a 3-nm-thick Ir(dmppy-ph)2tmd and DIC-TRZ-doped yellow light-emitting layer 6, a 15-nm-thick TDBA-DI and PPF-doped blue light-emitting layer 7, a 5-nm-thick PPF hole blocking layer / electron transport layer 8, and a 50-nm-thick Tm3PyP26PyB electron transport layer 9 were sequentially deposited on the ITO layer. Next, the unfinished device was transferred to a metal evaporation chamber and deposited at a temperature less than 1.0×10 -5A 1 nm thick LiF electron injection layer 10 is evaporated in a vacuum atmosphere of 3.5 Pa, and finally a 100 nm thick Al metal cathode layer 11 is evaporated on the LiF layer through a special mask to prepare a white organic electroluminescent device with a structure of ITO / HAT-CN / TAPC / TCTA / Ir(dmppy-ph)2tmd(3wt%):DIC-TRZ / TDBA-DI(25wt%):PPF / PPF / Tm3PyP26PyB / LiF / Al. The evaporation rate of HAT-CN in the hole injection layer 3 is controlled at 0.01 nm / s, the evaporation rate of TAPC in the hole transport layer 4 is controlled at 0.05 nm / s, the evaporation rate of TCTA in the hole transport layer / electron blocking layer 5 is controlled at 0.05 nm / s, the evaporation rates of Ir(dmppy-ph)2tmd and DIC-TRZ in the yellow light-emitting layer 6 are controlled at 0.0015 nm / s and 0.05 nm / s, respectively, and the evaporation rates of TD in the blue light-emitting layer 7 are controlled at 0.01 nm / s and 0.05 nm / s, respectively. The evaporation rates of BA-DI and PPF are controlled at 0.0125 nm / s and 0.05 nm / s respectively, the evaporation rate of PPF in the hole blocking layer / electron transport layer 8 is controlled at 0.05 nm / s, the evaporation rate of Tm3PyP26PyB in the electron transport layer 9 is controlled at 0.05 nm / s, the evaporation rate of LiF in the electron injection layer 10 is controlled at 0.005 nm / s, and the evaporation rate of Al in the metal cathode layer 11 is controlled at 0.5 nm / s.

[0107] Fig.11 This is a schematic diagram of the structure of the white light device prepared in Example 3, in which the white light device uses TADF material as the main body of the yellow light phosphorescent emission material and blue TADF material as the blue light-emitting unit, and is composed of a glass substrate 1, an anode layer 2, a hole injection layer 3, a hole transport layer 4, a hole transport layer / electron blocking layer 5, a yellow light-emitting layer 6, a blue light-emitting layer 7, a hole blocking layer / electron transport layer 8, an electron transport layer 9, an electron injection layer 10 and a metal cathode layer 11 which are connected in sequence.

[0108] Fig.12 This is a current efficiency-current density-power efficiency characteristic curve of the white light device prepared in Example 3. The results show that the maximum current efficiency of the white light device is 105.67 candelas / ampere (cd / A), and the maximum power efficiency is 114.68 lumens / watt (lm / W). Fig.13 The external quantum efficiency-current density characteristic curve of the device shows that the maximum external quantum efficiency of the device is 35.72%. In addition, at a brightness of 1000 candelas / square meter, the current efficiency of the device is 91.38 candelas / ampere (cd / A), the power efficiency is 71.73 lumens / watt (lm / W), and the external quantum efficiency is 32.03%. Fig.14 The white light device prepared in Example 3 has a brightness of 1000 cd / m2 , 2000cd / m 2 and 5000cd / m 2 The spectrum diagram shows that the two main emission peaks in the spectrum are located at 476 and 564 nanometers, the device color coordinates are (0.392, 0.435), (0.383, 0.430), and (0.367, 0.420), the color rendering index is 54, and the color temperature is 4062K.

[0109] Fig.15 The brightness-current density-voltage characteristic curve of the device in Example 3 shows that the lighting voltage of the device is 2.5V and the maximum brightness of the device is 77775cd / m 2 .

[0110] Example 4

[0111] First, the ITO glass with patterns was cleaned with cleaning solution and deionized water for 15 minutes and then placed in an oven for drying. Then, the dried substrate was placed in a pretreatment vacuum chamber and then transferred to an organic evaporation chamber. -5 In an organic evaporation chamber at 1000 rpm, a 6-nm-thick HAT-CN hole injection layer 3, a 50-nm-thick TAPC hole transport layer 4, a 10-nm-thick TCTA hole transport layer / electron blocking layer 5, a 3-nm-thick Ir(dmppy-ph)2tmd and DIC-TRZ-doped yellow light-emitting layer 6, a 15-nm-thick TDBA-DI and PPF-doped blue light-emitting layer 7, and a 50-nm-thick Tm3PyP26PyB hole blocking layer / electron transport layer 8 were sequentially deposited on the ITO layer. Next, the unfinished device was transferred to a metal evaporation chamber and deposited at a temperature less than 1.0×10 -5A 1 nm thick LiF electron injection layer 9 is evaporated in a vacuum atmosphere of 300 Pa, and finally a 100 nm thick Al metal cathode layer 10 is evaporated on the LiF layer through a special mask to prepare a white organic electroluminescent device with a structure of ITO / HAT-CN / TAPC / TCTA / Ir(dmppy-ph)2tmd(3wt%):DIC-TRZ / TDBA-DI(25wt%):PPF / Tm3PyP26PyB / LiF / Al. The evaporation rate of HAT-CN in the hole injection layer 3 is controlled at 0.01 nm / s, the evaporation rate of TAPC in the hole transport layer 4 is controlled at 0.05 nm / s, the evaporation rate of TCTA in the hole transport layer / electron blocking layer 5 is controlled at 0.05 nm / s, the evaporation rates of Ir(dmppy-ph)2tmd and DIC-TRZ in the yellow light-emitting layer 6 are controlled at 0.0015 nm / s and 0.05 nm / s, respectively, the evaporation rates of TDBA-DI and PPF in the blue light-emitting layer 7 are controlled at 0.0125 nm / s and 0.05 nm / s, respectively, the evaporation rate of Tm3PyP26PyB in the hole blocking layer / electron transport layer 8 is controlled at 0.05 nm / s, the evaporation rate of LiF in the electron injection layer 9 is controlled at 0.005 nm / s, and the evaporation rate of Al in the metal cathode layer 10 is controlled at 0.5 nm / s.

[0112] Fig.16 It is a structural schematic diagram of a white light device, in which TADF material is used as the main body of yellow light phosphorescent emitting material and blue TADF material is used as the blue light emitting unit, and the device is composed of a glass substrate 1, an anode layer 2, a hole injection layer 3, a hole transport layer 4, a hole transport layer / electron blocking layer 5, a yellow light emitting layer 6, a blue light emitting layer 7, a hole blocking layer / electron transport layer 8, an electron injection layer 9 and a metal cathode layer 10 which are connected in sequence.

[0113] Fig.17 The current efficiency-current density-power efficiency characteristic curve of the white light device prepared in Example 4 shows that the maximum current efficiency of the white light device is 106.88 candelas / ampere (cd / A), and the maximum power efficiency is 114.88 lumens / watt (lm / W). Fig.18 The external quantum efficiency-current density characteristic curve of the device shows that the maximum external quantum efficiency of the device is 35.59%. In addition, at a brightness of 1000 candelas / square meter, the current efficiency of the device is 90.53 candelas / ampere (cd / A), the power efficiency is 74.81 lumens / watt (lm / W), and the external quantum efficiency is 30.95%. Fig.19 The white light device prepared in Example 4 has a brightness of 1000 cd / m 2 , 2000cd / m 2 and 5000cd / m2 The spectrum diagram shows that the two main emission peaks in the spectrum are located at 476 and 564 nanometers, the device color coordinates are (0.412, 0.447), (0.403, 0.442), and (0.388, 0.433), the color rendering index is 51, and the color temperature is 3738K.

[0114] Fig. 20 The brightness-current density-voltage characteristic curve of the device in Example 4 shows that the lighting voltage of the device is 2.5V and the maximum brightness of the device is 71636cd / m 2 .

[0115] Example 5

[0116] First, the ITO glass with patterns was cleaned with cleaning solution and deionized water for 15 minutes and then placed in an oven for drying. Then, the dried substrate was placed in a pretreatment vacuum chamber and then transferred to an organic evaporation chamber. -5 In the organic evaporation chamber of Pa, a 6-nm thick HAT-CN hole injection layer 3, a 50-nm thick TAPC hole transport layer 4, a 10-nm thick TCTA hole transport layer / electron blocking layer 5, a 3-nm thick PQ2Ir(dpm) and DIC-TRZ doped red light-emitting layer 6, a 3-nm thick Ir(mppy)3 and DIC-TRZ doped green light-emitting layer 7, a 15-nm thick TDBA-DI and PPF doped blue light-emitting layer 8, a 5-nm thick PPF hole blocking layer / electron transport layer 9, and a 50-nm thick Tm3PyP26PyB electron transport layer 10 were sequentially deposited on the ITO layer.

[0117] Next, the unfinished device is transferred to a metal deposition chamber and -5A 1 nm thick LiF electron injection layer 11 is evaporated in a vacuum atmosphere of 300 Pa, and finally a 100 nm thick Al metal cathode layer 12 is evaporated on the LiF layer through a special mask to prepare a white organic electroluminescent device with a structure of ITO / HAT-CN / TAPC / TCTA / PQ2Ir(dpm)(3wt%):DIC-TRZ / Ir(mppy)3(10wt%):DIC-TRZ / TDBA-DI(25wt%):PPF / PPF / Tm3PyP26PyB / LiF / Al. The evaporation rate of HAT-CN in the hole injection layer 3 was controlled at 0.01 nm / s, the evaporation rate of TAPC in the hole transport layer 4 was controlled at 0.05 nm / s, the evaporation rate of TCTA in the hole transport layer / electron blocking layer 5 was controlled at 0.05 nm / s, the evaporation rates of PQ2Ir(dpm) and DIC-TRZ in the red light-emitting layer 6 were controlled at 0.0015 nm / s and 0.05 nm / s, respectively, and the evaporation rates of Ir(mppy)3 and DIC-TRZ in the green light-emitting layer 7 were controlled at 0.005 nm / s, respectively. The evaporation rates of TDBA-DI and PPF in the blue light-emitting layer 8 are controlled at 0.0125 nm / s and 0.05 nm / s respectively, the evaporation rate of PPF in the hole blocking layer / electron transport layer 9 is controlled at 0.05 nm / s, the evaporation rate of Tm3PyP26PyB in the electron transport layer 10 is controlled at 0.05 nm / s, the evaporation rate of LiF in the electron injection layer 11 is controlled at 0.005 nm / s, and the evaporation rate of Al in the metal cathode layer 12 is controlled at 0.5 nm / s.

[0118] Fig.21 This is a schematic diagram of the structure of a white light device prepared in Example 5, in which the white light device uses TADF material as the main body of red and green phosphorescent emission materials and blue TADF material as the blue light-emitting unit, and is composed of a glass substrate 1, an anode layer 2, a hole injection layer 3, a hole transport layer 4, a hole transport layer / electron blocking layer 5, a red light-emitting layer 6, a green light-emitting layer 7, a blue light-emitting layer 8, a hole blocking layer / electron transport layer 9, an electron transport layer 10, an electron injection layer 11 and a metal cathode layer 12, which are connected in sequence. Fig. 22 This is a current efficiency-current density-power efficiency characteristic curve of the white light device prepared in Example 5. The results show that the maximum current efficiency of the white light device is 63.75 candelas / ampere (cd / A), and the maximum power efficiency is 55.61 lumens / watt (lm / W). Fig.23The external quantum efficiency-current density characteristic curve of the device shows that the maximum external quantum efficiency of the device is 28.91%. In addition, at a brightness of 1000 candelas / square meter, the current efficiency of the device is 54.91 candelas / ampere (cd / A), the power efficiency is 35.92 lumens / watt (lm / W), and the external quantum efficiency is 25.36%. Fig.24 The white light device prepared in Example 5 has a brightness of 1000 cd / m 2 , 2000cd / m 2 , 5000cd / m 2 、10000cd / m 2 and 20000cd / m 2 The results show that the three main emission peaks in the spectrum are located at 476, 504 and 596 nanometers, respectively. The device color coordinates are (0.363, 0.385), (0.363, 0.384), (0.361, 0.383), (0.359, 0.381) and (0.361, 0.381), respectively. The color rendering index is 79 and the color temperature is 4545K. 2 Within the brightness range, the CIE coordinate change is only (0.003, 0.004). By using PPF as the hole blocking layer / electron transport layer 9, the carrier recombination area and energy transfer process can be better adjusted, making the white light device have better performance and better color stability. Fig.25 The brightness-current density-voltage characteristic curve of the device in Example 5 shows that the lighting voltage of the device is 3 volts and the maximum brightness of the device is 65487 cd / m 2 .

[0119] The above embodiments are only used to help understand the method and core idea of ​​the present invention. It should be noted that, for those skilled in the art, several improvements and modifications can be made to the present invention without departing from the principles of the present invention, and these improvements and modifications also fall within the scope of protection of the claims of the present invention.

Claims

1. A white light emitting layer material, characterized in that: It is composed of a red light-emitting layer, a green light-emitting layer, and a blue light-emitting layer in sequence, or it is composed of a yellow light-emitting layer and a blue light-emitting layer in sequence; The red light-emitting layer is composed of a TADF main material and a red phosphorescent light-emitting material; The green light-emitting layer is composed of a TADF main material and a green phosphorescent light-emitting material; The blue light-emitting layer is composed of a host material containing a phosphorus-oxygen double bond and a blue TADF light-emitting material; The yellow light-emitting layer is composed of a TADF main material and a yellow phosphorescent light-emitting material.

2. The white light emitting layer material according to claim 1, characterized in that: The TADF host material is selected from 2,4-diphenyl-6-bis((12-phenylindole)[2,3-a]carbazole-11-yl)-1,3,5-triazine, 11-(3-(4,6-di([1,1'-biphenyl]-3-yl)-1,3,5-triazine-2-yl)phenyl)-12,12-dimethyl-11,12-dihydroindeno[2,1-a]carbazole, 11-(4,6-di(biphenyl-4-yl)-1,3,5-triazine-2-yl)-12-phenyl-11,12-dihydroindole[2,3-a]carbazole, 11-(4,6-di(biphenyl-3-yl)-1,3,5-triazine-2-yl)-12-phenyl-11,12-dihydroindole[2,3-a]carbazole, a]carbazole, 5-(3-(4,6-diphenyl-1,3,5-triazine-2-yl)phenyl)-7,7-dimethyl-5,7-dihydroindeno[2,1-b]carbazole, 5-(4,6-diphenyl-1,3,5-triazine-2-yl)-11-phenyl-5,11-dihydroindeno[3,2-b]carbazole, 9-(4-(4,6-diphenyl-1,3,5-triazine-2-yl)phenyl)-9H-carbazole, 2-(3-(4,6-diphenyl-1,3,5-triazine-2-yl)phenyl)-1-phenyl-1H-benzo[d]imidazole, 3-[3-(9H-carbazole-9-yl)phenyl]furo[2,3-b:5,4-b']bipyridine; The main material containing phosphorus-oxygen double bonds in the blue light-emitting layer is selected from one or more of 2,8-bis(diphenylphosphino)dibenzo[b,d]furan, bis[2-(diphenylphosphino)phenyl]ether oxide, diphenyl-4-triphenylsilyl-phenyl-phosphine oxide, dibenzofuran-4-yl-diphenyl-phosphine oxide, 9,9-spirobifluorene-4-yl-diphenyl-phosphine oxide, 9-(3,5-bis(diphenylphosphino)phenyl)-9H-carbazole, and 2,8-bis(diphenylphosphino)dibenzo[b,d]thiophene.

3. The white light emitting layer material according to claim 2, characterized in that: The red phosphorescent luminescent material is selected from one or more of bis(2-benzo[b]thiophene-2-ylpyridine)(acetylacetonate)iridium(III), tris(1-phenylisoquinoline)iridium(III), bis(2-phenylquinoline)(2,2,6,6-tetramethylheptane-3,5-dioate)iridium(III), bis(phenylisoquinoline)(2,2,6,6-tetramethylheptane-3,5-dioate)iridium(III), bis(2-methyldibenzo[f,h]quinoxaline)(acetylacetonate)iridium(III), bis(2-(3,5-dimethylphenyl)quinoline-C2,N')(acetylacetonate)iridium(III), and bis[2-(3,5-dimethylphenyl)-4-methylquinoline](acetylacetonate)iridium(III); The green phosphorescent luminescent material is selected from one or more of bis(2-phenylpyridine)(acetylacetonate)iridium(III), tris[2-(p-tolyl)pyridine]iridium(III), bis(2-(3,5-dimethylphenyl)-4-propylpyridine)(2,2,6,6-tetramethylheptane-3,5-diketonate)iridium(III), bis(2-(naphthalene-2-yl)pyridine)(acetylacetonate)iridium(III), [2-(4-methyl-5-phenyl-2-pyridyl-KN)phenyl KC]bis[2-(2-pyridyl-KN)phenyl KC]iridium; The blue TADF luminescent material is selected from 10-(2,12-di-tert-butyl-5,9-dioxa-13b-boronaphtho[3,2,1-de]anthracen-7-yl)-9,9-dimethyl-9,10-dihydroacridine, 5-(2,12-di-tert-butyl-5,9-dioxa-13b-boronaphtho[3,2,1de]anthracen-7-yl)-10,15-diphenyl-10,15-dihydro-5H diindole[3,2-a:3',2'-c]carbazole, 9'-(2,12-di-tert-butyl-5,9-dioxa-13b-boronaphthyl-[3,2,1de]anthracen-7-yl)-9,9'-diphenyl-9H,9'H,9'-H-3,3':6',3'-dicarbazole, 10,10'-(4,4'-sulfonylbis(4,1-phenylene))bis(9,9-dimethyl-9,10 -dihydroacridine), 9'-[4-(4,6-diphenyl-1,3,5-triazine-2-yl)phenyl]-3,3", 6,6'-tetraphenyl-9,3':6',9'-tert-9H-carbazole, (9'-(2,12-di-tert-butyl-5,9-dioxa-13b-boronaphtho[3,2,1-de]anthracen-7-yl)-9'H-9,3':6',9'-dicarbazole, 5-(3, One or more of 11-dimethyl-5,9-dioxa-13b-boronaphtho[3,2,1-de]anthracene-7-yl)-10,15-diphenyl-10,15-dihydro-5H-diindolyl[3,2-a:3',2'-c]carbazole, 3,11-bis(1,3,6,8-tetramethyl-9H-carbazole-9-yl)-5,9-dioxa-13b-boronaphtho[3,2,1-de]anthracene; The yellow phosphorescent light-emitting material is selected from iridium (III) bis(2-(3,5-dimethylphenyl)-4-phenylpyridine)(2,2,6,6-tetramethylheptane-3,5-dionate), iridium (III) acetylacetonate, bis(4-(4-tert-butylphenyl)thieno[3,2-c]-pyridinyl-N, C2'), bis(4-phenylthieno[3,2-c]pyridinyl-N, C2')(acetylacetonate), iridium (III) bis(2-(2,4-difluorophenyl)quinoline)picolinate, bis(2-(9,9-diethylfluoren-2-yl)-1-phenyl-1H-benzo[d]imidazole)(acetylacetonate), iridium (III) acetylacetonate, bis(4-(4-tert-butylphenyl)thieno[3,2-c]pyridinyl-N, C2').

4. The white light emitting layer material according to claim 1, characterized in that: The red phosphorescent luminescent material is selected from bis(2-phenylquinoline)(2,2,6,6-tetramethylheptane-3,5-dioate)iridium(III); The green phosphorescent luminescent material is selected from tris[2-(p-tolyl)pyridine]iridium(III); The blue TADF luminescent material is selected from 5-(2,12-di-tert-butyl-5,9-dioxa-13b-boronaphtho[3,2,1de]anthracene-7-yl)-10,15-diphenyl-10,15-dihydro-5H diindole[3,2-a:3',2'-c]carbazole; The yellow phosphorescent light-emitting material is selected from bis(2-(3,5-dimethylphenyl)-4-phenylpyridine)(2,2,6,6-tetramethylheptane-3,5-diketonate)iridium(III).

5. The white light emitting layer material according to claim 1, characterized in that: The red light-emitting layer is composed of bis(2-phenylquinoline)(2,2,6,6-tetramethylheptane-3,5-dioate)iridium(III) and 2,4-diphenyl-6-bis((12-phenylindole)[2,3-a]carbazole-11-yl)-1,3,5-triazine; The green light-emitting layer is composed of tris[2-(p-tolyl)pyridine]iridium(III) and 2,4-diphenyl-6-bis((12-phenylindole)[2,3-a]carbazole-11-yl)-1,3,5-triazine; The blue light-emitting layer is composed of 5-(2,12-di-tert-butyl-5,9-dioxa-13b-boronaphtho[3,2,1de]anthracene-7-yl)-10,15-diphenyl-10,15-dihydro-5H diindole[3,2-a:3',2'-c]carbazole and 2,8-bis(diphenylphosphoryl)dibenzo[b,d]furan; The yellow light-emitting layer is composed of bis(2-(3,5-dimethylphenyl)-4-phenylpyridine)(2,2,6,6-tetramethylheptane-3,5-dionatoic acid)iridium(III) and 2,4-diphenyl-6-bis((12-phenylindole)[2,3-a]carbazole-11-yl)-1,3,5-triazine.

6. The white light emitting layer material according to any one of claims 1 to 5, characterized in that: The content of the red phosphorescent material in the red light-emitting layer is 1wt% to 10wt%; The content of the green phosphorescent material in the green light-emitting layer is 1wt% to 25wt%; The content of the blue TADF luminescent material in the blue luminescent layer is 5wt% to 50wt%; The content of the yellow phosphorescent material in the yellow light emitting layer is 1 wt% to 20 wt%.

7. The white light emitting layer material according to any one of claims 1 to 5, characterized in that: The thickness of the red light emitting layer is selected from 2-20 nm; The thickness of the green light emitting layer is selected from 2-20 nm; The thickness of the blue light-emitting layer is selected from 5-40 nm; The thickness of the yellow light emitting layer is selected from 1-30 nm.

8. A white light organic electroluminescent device, characterized in that: The white light emitting layer material comprises the white light emitting layer material according to any one of claims 1 to 7.

9. The white light organic electroluminescent device according to claim 8, characterized in that: The white light organic electroluminescent device further comprises a hole transport layer / electron blocking layer, a hole transport layer, and a hole injection layer sequentially connected below the white light emitting layer material, and a hole blocking layer / electron transport layer and an electron injection layer sequentially connected above the white light emitting layer material; Wherein, the hole transport layer / electron blocking layer is selected from one or more of 4,4',4"-tris(carbazole-9-yl)triphenylamine, 9,9'-(1,3-phenyl)di-9H-carbazole, 4,4'-bis(carbazole-9-yl)biphenyl, and 9-(4-tert-butylphenyl)-3,6-bis(triphenylsilyl)-9H-carbazole; The hole blocking layer / electron transport layer is selected from one or more of 2,8-bis(diphenylphosphoryl)dibenzo[b,d]furan, 1,3,5-tris(6-(3-(pyridin-3-yl)phenyl)pyridin-2-yl)benzene, 2,4,6-tris(3'-(pyridin-3-yl)biphenyl-3-yl)-1,3,5-triazine, 1,3,5-tris[(3-pyridine)-3-phenyl]benzene, and 1,3,5-tris(1-phenyl-1H-benzimidazol-2-yl)benzene.

10. Use of the white light organic electroluminescent device according to claim 8 or 9 in eye protection lamps and vehicle lighting lamps.